A visit to the our stage festival: Participation, inclusion and sharing at the Bürgerbühne Dresden - Pipinia, Ioulia (The Historical Review/La Revue Historique, 2020)
In 2009 Staatsschauspiel Dresden, the state theatre of Saxony, became the first playhouse in Germany to include, in the company’s structure and repertoire, a Bürgerbühne, a stage dedicated to documentary and participatory theatre. Within ten years, Dresden’s prolific and acclaimed model of a citizens’ stage became a thriving and active example of inclusion and participation in theatre arts. In May 2019, Our Stage, the 4th European festival of, and on, citizens’ theatre was held in Dresden, offering a full week of performances, seminars, talks, workshops and discussions on various aspects of participatory theatre. The article offers a partial account of the festival and its performances in order to trace recent developments in applied, documentary and participatory theatre; it also tentatively attempts to address the notions of participation, inclusion and sharing in relation to contemporary Greek theatre and its performances.